Broadband optical spin dependent reflection in self-assembled GaAs-based nanowires asymmetrically hybridized with Au - Emilija Petronijevic (Nature Portfolio, 2021)
Abstract Hybridization of semiconductor nanostructures with asymmetric metallic layers offers new paths to circular polarization control and chiral properties. Here we study, both experimentally and numerically, chiral properties of GaAs-based nanowires (NWs) which have two out of six sidewalls covered by Au. Sparse ensembles of vertical, free-standing NWs were fabricated by means of lithography-free self-assembled technique on Si substrates and subsequently covered by Au using tilted evaporation. We report on optical spin-dependent specular reflection in the 680–1000 nm spectral range when the orientation of the golden layers follows the rule of extrinsic chirality. The analysis shows reflection peaks of the chiral medium whose intensity is dependent on the light handedness. We further propose a novel, time-efficient numerical method that enables a better insight into the far-field intensity and distribution of the scattered light from a sparse NW ensembles. The measurements done on three different samples in various orientations show good agreement with theoretical predictions over a broad wavelength range.